Molecular mechanism and potential application of bacterial infection in the silkworm, Bombyx mori. (June 2022) - Wang, Qiang; Sun, Zhonghe; Ma, Shangshang; Liu, Xiaoyong; Xia, Hengchuan; Chen, Keping
Abstract: As a representative species of Lepidoptera, Bombyx mori has been widely studied and applied. However, bacterial infection has always been an important pathogen threatening the growth of silkworms. Bombyx mori can resist various pathogenic bacteria through their own physical barrier and innate immune system. However, compared with other insects, such as Drosophila melanogaster, research on the antibacterial mechanism of silkworms is still in its infancy. This review systematically summarized the routes of bacterial infection in silkworms, the antibacterial mechanism of silkworms after ingestion or wounding infection, and the intestinal bacteria and infection of silkworms. Finally, we will discuss silkworms as a model animal for studying bacterial infectious diseases and screening antibacterial drugs. Highlights: Route of bacterial infection in silkworms. Molecular mechanism of bacterial infection in silkworms. Silkworms as an animal model for studying bacterial infectious. Silkworms as an animal model for screening for antibacterial drugs.